ANALISIS DAMPAK MEKANISME PENERIMAAN SISWA BARU BERDASARKAN UMUR DI INDONESIA KHUSUSNYA DI JAKARTA - Muhammad Salman Al Farisyi; Achmad Fawaz Ferdiansyah; Andhika Rahadian; Dhanurangga Al Fadh; Yasyfiana Fariha Putrisusari; Ernawati Ernawati (Journal Publicuho, 2021)
New Student Admission is a series of annual compulsory activities held by all schools in Indonesia in order to accept new students in the new academic year. The process of New Student Admission is based on school and government policies. In 2019, the Ministry of Education and Culture issued a regulation regarding the admission of new students as stipulated in the Regulation of the Minister of Education and Culture Number 44 of 2019. In this regulation, the age of students is used as one of the parameters that are put into consideration after the distance between residence. In its implementation, many schools in Jakarta use age as the main parameter instead of the distance of student residence so that it violates the provisions of Permendikbud 44 of 2019. The use of age as a main parameter can affect student achievement in school. To see this further, a literature study was conducted which discussed the effect of entry age and achievement in several countries and various levels of education. Based on the literature that has been done, it is unfortunate that the effect of student entry age on achievement at school has different results between each level of education. At the early education level (Kindergarten - Elementary School), the age at which students enter has an influence on their achievement at school, but this does not apply at the secondary level (Junior High School - Senior High School) where the age of students has no effect on achievement at school.